2019
DOI: 10.33736/jcest.1067.2019
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Structural Performance of Sandwich Concrete Panels Subjected to Blast Load Considering Dynamic Increase Factor

Abstract: The safety of the civil structures could be significantly improved against shock waves and blast loads by using steel concrete steel (SCS) protective walls. A numerical study has been performed to simulate the response of SCS wall subjected to a near-field blast load. A conventional SCS panel subjected to near-field blast load and its structural performance is evaluated in terms of maximum damage and deformation. The simulations performed using ABAQUS\EXPLICIT finite element package and built-in concrete damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Te bioinspired sandwich construction on an aluminium face sheet with glass fbre reinforcement, epoxy resin matrix, and pet foam core material is the focus of this research [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Te materials' characteristics were determined experimentally in accordance with ASTM standards [31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Te bioinspired sandwich construction on an aluminium face sheet with glass fbre reinforcement, epoxy resin matrix, and pet foam core material is the focus of this research [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Te materials' characteristics were determined experimentally in accordance with ASTM standards [31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the use of the proposed wall configuration will have better performance than conventional walls, while there is little extra cost to make it. [13]. Yang et al ( 2019) during a case study collected the results of 491 concrete filled steel tube (CFT) column test results under axial load from existing literature.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal parameter for each of the structural components is identified using a specific optimization method. It was concluded that using the proposed wall configuration compares with the regular walls will have better performance while its additional construction costs is insignificant [12]. Yang et al ( 2019), carried out a case study of 491 test results of the CFT under axial load from the available literature.…”
mentioning
confidence: 99%